The handling of upland soils - Cottrell, Ernest Lerned (My University, 1899)
Introduction: How to handle upland soils is a question which is forcing itself upon many farmers. It is a question of vital importance and one that many of us must answer immediately. As population increases land rises in value so that the poorer land must be brought into use. While this is true, the prices of farm products are declining and the necessities of the farmer are on the increase. He must have more home comforts, dress better, and give his children a better education than he or his fore fathers had. It can readily be seen that in order to supply these wants and meet the demands of civilization the farmer must increase his income; and the only way to do this, is to increase the production from the soil. Before taking up this subject of increasing the productivity of the soil, let us take a look at the fields and see in what condition they now are, and what has brought about these conditions.
Citation: Cottrell, Ernest Lerned. The handling of upland soils. Senior thesis, Kansas State Agricultural College, 1899.
Morse Department of Special Collections
Keywords: Deteriation of Soils; Restoring Fertility; Action of Frost; Rotation; Theses; Manuscripts (documents)